DEFINING REGULATING PARAMETERS OF SODIUM DITHIONYTE Na2S2O4 - Mustafa Burgić; Amir Fazlić; Jasminka Sadadinović; Mirela Burgić-Salihović (Journal of Engineering & Processing Management, 2014)
Dithionites of sodium and zinc (Na2S2O4 and ZnS2O4), also known asn hydrosulphites, are efficient reducing materials widely used in various industries.Mosto common application of Na2S2O4 is in textile industry and also as important ingredient in painting, printing and bleaching materials. In pharmacy it is widely used for drugs synthesis, in foof industry for fruit syrups bleaching, edible oil and gelatyne. During the experiment we tested parameters of Na2S2O4 dithionites synthesis by reducing sulphuric acis with zinc powder. Results of experiment clearly indicate that most appropriate temperature for synthesis is around 400C, reaction time 65 minutes at constant mixer speed and continuous cooling.
Keywords: dithioonites of sodium zinc; reducing materials; sulphuric acid; zinc powder; synthesis; temperature regime